The effect of quality management on patient loyalty in selected Jordanian private hospitals - Al-Mhasnah, Anas Musleh Marzoq
The effect of quality management (QM) on customer satisfaction, customer loyalty, and quality of health service has been emphasised by numerous researchers. Several studies have been carried out, including in Jordanian hospitals. According to the Ministry of Health Jordan, revenue from the medical tourism sector in 2017 decreased from 38% to 20%. By the end of 2016, patient satisfaction (PS) had dropped from 81 % to 79%. Furthermore, patient loyalty (PL) d creased from 5.1 % to 4.8%, as reported by the Private Hospitals Association Jordan. Thus, this study aimed to determine the effect of QM on PL in selected private hospitals in Jordan. Specifically, this study tested the role of PS and hospital service quality (HSQ) as mediating variables in the relationship between QM and PL. These mediators were selected according to the results of many previous studies, which menti ned the effective role of customer satisfaction and/or HSQ in the relationship between QM and PL. The Malcolm Baldrige criteria and S RVQUAL theory were used in this study. Besides that, the study also used a quantitative approach through the distribution of questionnaires to achieve the research objectives. The sample comprised of 400 patients obtained using a simple random sampling method from five private hospitals. A total of276 or 69% of the questionnaires were successfully retrieved. This study elaborated the research phenomenon b analysing the obtained data to identify the effect of the relationship between the con tructs using the Amos 21 software. There were statistically significant effects of QM on HSQ, QM on PS, HSQ on PS, and PS on PL at 0.05 significance le~el. Nevertheless, the effect of QM on PL and HSQ on PL was not significant at the 0.05 level. Meanwhile, there was mediation by PS on the relationships between QM and HSQ and QM and PL. HSQ played a mediating role in the relationship between QM and PS but not between QM and PL. In several previous studies, PL has been found to playa major role. The process of PL is the main goal towards achieving a profitable return in the health sector, based on the initial achievement ofPS. Based on the findings, this study developed a new integrated theoretical framework, which combined the factors affecting PL and provided empirical support for the mediating role ofPS. From the perspective of patients who have been hospitalised in Jordan, QM and HSQ are important and useful to those who regularly return to the hospital due to their satisfaction and loyalty.